2009
DOI: 10.1002/jcp.21785
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac neural stem cell phenotype is compromised in streptozotocin‐induced diabetic cardiomyopathy

Abstract: Neural stem cells were identified in the rat heart and during scar formation and healing participated in sympathetic fiber sprouting and angiogenesis. In the setting of diabetes, impaired wound healing represents a typical pathological feature. These findings provided the impetus to test the hypothesis that experimental diabetes adversely influenced the phenotype of cardiac neural stem cells. Streptozotocin (STZ)-induced diabetic rats were associated with elevated plasma glucose levels, significant loss of bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The upregulation of nestin in adult ventricular fibroblasts could lead to excessive proliferation and contribute in part to reactive fibrosis (41,49). A seminal feature of diabetes is impaired wound healing, and El-Helou and colleagues (22) reported the loss of nestin protein and mRNA expression in cardiac neural progenitor/stem cells in rat models of type I and type II diabetes. In this context, it is tempting to speculate that nestin-depleted neural progenitor/stem cells may predispose the diabetic heart to an inadequate reparative fibrotic response following ischemic damage.…”
Section: Resultsmentioning
confidence: 99%
“…The upregulation of nestin in adult ventricular fibroblasts could lead to excessive proliferation and contribute in part to reactive fibrosis (41,49). A seminal feature of diabetes is impaired wound healing, and El-Helou and colleagues (22) reported the loss of nestin protein and mRNA expression in cardiac neural progenitor/stem cells in rat models of type I and type II diabetes. In this context, it is tempting to speculate that nestin-depleted neural progenitor/stem cells may predispose the diabetic heart to an inadequate reparative fibrotic response following ischemic damage.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental type I diabetes was induced following a single injection of streptozotocin (60 mg/kg) in the jugular vein of adult male Sprague-Dawley rats (9–11 weeks old) [15,16]. Plasma glucose levels and left ventricular function were determined as previously described [16].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Oikawa and colleagues demonstrated that nestin was expressed in vascular smooth muscle cells of the adult rat aorta [14]. Work from our lab detected a population of cardiac resident nestin-expressing cells that exhibited a neural progenitor/stem cell phenotype and downregulation of the intermediate filament protein was identified as an incipient pathophysiological event of type I diabetes [8,9,15,16]. Based on these observations, the present study tested the hypothesis that nestin expression in vascular smooth muscle cells (VSMCs) of the adult rat carotid artery and aorta was directly linked to proliferation and the intermediate filament protein was downregulated during the early stage of experimental type I diabetes attributed to hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…45 We and others also found reduced NGF in diabetic hearts which might explain the cardiac sensory denervation and neuropathy reported in diabetic patients. 55,[57][58][59] …”
Section: Gdnf Signaling Regulates Parasympathetic Innervation and Ngfmentioning
confidence: 99%